Discrete Spectral Local Measurement Method for Testing Solar Concentrators - Huifu Zhao; Hua Liu; Lei Jing; Ying Liu; Chun Li; Zhenwu Lu; Qiang Sun (International Journal of Photoenergy)
In order to compensate for the inconvenience and instability of outdoor photovoltaic concentration test system which are caused by the weather changes, we design an indoor concentration test system with a large caliber and a high parallelism, and then verify its feasibility and scientificity. Furthermore, we propose a new concentration test method: the discrete spectral local measurement method. A two-stage Fresnel concentration system is selected as the test object. The indoor and the outdoor concentration experiments are compared. The results show that the outdoor concentration efficiency of the two-stage Fresnel concentration system is 85.56%, while the indoor is 85.45%. The two experimental results are so close that we can verify the scientificity and feasibility of the indoor concentration test system. The light divergence angle of the indoor concentration test system is 0.267° which also matches with sunlight divergence angle. The indoor concentration test system with large diameter (145 mm), simple structure, and low cost will have broad applications in solar concentration field.